ANALISIS PENGGUNAAN BAHASA MINANG SEBAGAI BAHASA PENGANTAR DALAM PEMBELAJARAN BAHASA INDONESIA SISWA KELAS VI SD - Hafifa Yulia Andika; Ghaitsa Zahira Amalia Putri; Adrias Adrias (Cerdas Proklamator, 2026)
This study aims to describe the use of the Minang language as a medium of instruction in Indonesian language learning and its implications for the comprehension of sixth-grade students at SDN 04 Koto Tangah and SDN 22 Kampung Luar. This research employed a qualitative approach with a descriptive research design. Data were collected through in-depth interviews with sixth-grade teachers, classroom observations, and documentation. The data were analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The findings revealed that the Minang language was used as a supporting language in certain situations, particularly when students experienced difficulties understanding materials delivered in Indonesian. The use of the Minang language appeared through code-switching by teachers and code-mixing by students during the learning process. The use of the Minang language had positive impacts, such as improving students’ understanding of learning materials, increasing student participation, and creating a more communicative and comfortable classroom atmosphere. However, the dominant use of the Minang language also caused negative impacts, including phonological interference and code-mixing in students’ Indonesian language usage. To overcome these issues, teachers implemented several strategies, such as habituating students to use Indonesian consistently, providing contextual language corrections, and using the Minang language selectively as a learning aid. This study indicates that a balanced use of instructional languages can support the effectiveness of Indonesian language learning in bilingual environments.